The Co-optation of Tecumseh: The War of 1812 and Racial Discourses in Upper Canada - Brownlie, Robin (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2012)
The Shawnee leader Tecumseh is one of very few named Aboriginal figures who are accorded a place in Canadian history texts. In the years following the War of 1812, he was claimed by Upper Canadians as a war hero and symbol of the struggle with the United States, a “Noble Savage” whose life and death provided material for nation-building discourses. Through the analysis of two long poems about Tecumseh published in the 1820s, this essay examines the early stages of Upper Canada’s co-optation of Tecumseh as a component of its national identity. The valiant but ultimately savage character the poems depicted could inspire Upper Canadians and remind them of their wartime sacrifices, but he also served to mark off Indigenous people from the Euro-Canadians whose cultural superiority legitimated their possession of the colony’s lands and resources. These literary works produced a “Canadian” hero who could be incorporated as a national symbol for a settlement colony he never set out to defend, and whose massive expansion after his death he would have vigorously opposed.